(untitled) (Orinoquia, 2019)
In the production process of maize hybrid seed is requirement to do detasseling or removing the male inflorescence in maternal lines. During this process the loss of the upper leaves and accompanying the panicle occur, this leaf area loss negatively affects seed production and flat and round grains frequency in commercial calibers. This work analyses the behavior of a maternal line, progenitor of a commercial hybrid of conventional maize with white endosperm. This line was subjected to various treatments related with the loss of leaf area when removing the male inflorescence. The behavior of seed production and frequency of formation of flat and round F1 grains in the gauges that are commercially accepted in the market were estimated. The results showed that when there is loss of leaves on the maize plant when removing the panicle, physiologically the development based on yield is affected, however it can tolerate the loss of one to four leaves without representing statistical differences in yield. Similarly, the size frequencies of flat and round grains in F1 commercial seeds were not affected